Association between mandatory health examination attendance and diabetes treatment initiation among employees being treated for hypertension. Issue 1 (9th December 2020) - Yamana, Hayato; Ono, Sachiko; Okada, Akira; Jo, Taisuke; Yasunaga, Hideo
Abstract: Objectives: It is unclear whether mandatory health examination is effective for employees who are already being treated for chronic diseases. We focused on patients being treated for hypertension and evaluated the association between employer‐based health examination attendance and diabetes treatment initiation. Methods: Using a database that stores health insurance claims and health examination results of subscribers enrolled in society‐managed health insurance plans in Japan, we identified employees aged 40‐59 years who were being treated for hypertension when starting diabetes treatment from April 2012 to December 2016. A case‐crossover analysis was conducted using 90, 180, and 270 days prior to diabetes treatment initiation as reference points and 90 days after the mandatory health examination as the exposure period. We conducted a subgroup analysis by hemoglobin A1c (HbA1c) level and frequency of outpatient blood glucose testing before the mandatory health examination. Results: We identified 1464 individuals starting treatment for diabetes while on antihypertensive drugs. The overall odds ratio for starting diabetes treatment within 90 days of the health examination was 1.89 (95% confidence interval: 1.70‐2.10). The subgroup analysis showed that this odds ratio increased as HbA1c level increased and as blood glucose testing frequency decreased. Conclusions: Among employees starting treatment for diabetes while being treated for hypertension, employer‐based mandatory health examination attendance was associated with initiation of diabetes treatment. The health examinations may be functioning as a complement to screening in outpatient settings.